KETIMPANGAN GENDER DALAM PERTUMBUHAN EKONOMI - Aktaria, Erma; Handoko, Budiono Sri (Universitas Muhammdaiyah Surakarta, 2012)
The objective of this research is to analyze the gender inequality in 14 districts/ cities in Central Kalimantan Province by using the Gender Inequality Index (GII), which introduced by UNDP, to analyze the effect of gender inequality with economic growth and compare the use of the GII with the Gender Development Index and Gender Empowerment Measure (GEM) in relation to economic growth. This research uses panel data from 14 districts/cities during 2004-2007, the analytical methods used were descriptive statistics in analyzing gender inequality and statistical inference to explain the influence of gender inequality on economic growth. Descriptive analysis results showed that there are sharp gender inequality in every district/city. The results of regression analysis shows that there are negative and significant effect of gender inequality to economic growth. Gender inequality is statistically represented by a proxy of the GII is not as strong compared to a proxy of the two others.